Screening efficiency and rolling effects of a rotating screen drum used to process wet soft agglomerates. (February 2017) - Bellocq, B.; Ruiz, T.; Delaplace, G.; Duri, A.; Cuq, B.
Abstract: The rotating screen drums are largely used in most powder handling and processing industries. They are commonly used for size separation of granular materials. Objectives of the present work are to better understand both roles, screening efficiency and shaping effects and to investigate and model which process parameters are relevant when using an inclined rotating screen drum for processing wet couscous agglomerates. Durum wheat semolina was used as raw material to produce the wet agglomerates. The pilot rotating screen drum equipment was composed of two sieves to separate three fractions: fine, medium, and large agglomerates. The shaping effects of the rotating screen drum were evaluated from the measurements of the physico-chemical characteristics (size distribution, water content, compactness, and circularity) on wet soft agglomerates. To describe the screening efficiency parameters of a rotary screen drum, a specific method was developed by using a matrix analysis of the different measured weights of the collected products. The impacts of rotating screen drum parameters (angle of inclination, rotating speed, and product flow rate) on the sieving efficiency and on the shaping effects were investigated. The present results demonstrate high apparent screening efficiency of the rotating screen drum when used with wet agglomerates of durum wheat, ranging between 89 and 96% depending on the process conditions Finally, using dimensional analysis, two correlations were proposed on the circularity and the apparent screening efficiency whatever the operating conditions used (drum speed, angle of inclination and feed rate). Highlights: Screening efficiency of a rotating drum is measured by an original matrix analysis. The rotating drum is very efficient to screen wet soft agglomerates of wheat. The compactness and shape of the agglomerates are affected by the rolling process.